A Metabolic Imaging Study of Lexical and Phonological Naming Errors in Alzheimer Disease. (30th April 2020) - Isella, Valeria; Rosazza, Cristina; Gazzotti, Maria; Sala, Jessica; Morzenti, Sabrina; Crivellaro, Cinzia; Appollonio, Ildebrando Marco; Ferrarese, Carlo; Luzzatti, Claudio
Patients with Alzheimer disease (AD) produce a variety of errors on confrontation naming that indicate multiple loci of impairment along the naming process in this disease. We correlated brain hypometabolism, measured with 18fluoro-deoxy-glucose positron emission tomography, with semantic and formal errors, as well as nonwords deriving from phonological errors produced in a picture-naming test by 63 patients with AD. Findings suggest that neurodegeneration leads to: (1) phonemic errors, by interfering with phonological short-term memory, or with control over retrieval of phonological or prearticulatory representations, within the left supramarginal gyrus; (2) semantic errors, by disrupting general semantic or visual-semantic representations at the level of the left posterior middle and inferior occipitotemporal cortex, respectively; (3) formal errors, by damaging the lexical–phonological output interface in the left mid–anterior segment of middle and superior temporal gyri. This topography of semantic–lexical–phonological steps of naming is in substantial agreement with dual-stream neurocognitive models of word generation.